(untitled) (Malay Literature, 2025)
An extensive amount of classical Malay manuscripts are preserved in manuscript repositories both domestically and internationally. As such, most of them hold many Malay thoughts, knowledge, intellect, and culture that are yet to be studied and disseminated to the public. One classical Bruneian Malay manuscript titled Syair Kisah Negeri Brunei was discovered at the Borneo Research Centre (PenBorneo), Brunei History Centre. This manuscript has not received the attention of researchers and the public in exploring the views and thoughts contained within it. Therefore, this study aims to examine the extent to which Syair Kisah Negeri Brunei reflects the views and thoughts of Bruneian society by focusing on the leadership of the late Sultan Haji Omar ‘Ali Saifuddien as depicted in the syair. The study employs a hermeneutic approach as well as leadership characteristics outlined by Haji Mahmud Saedon (1995). The study found that the text of Syair Kisah Negeri Brunei contains views and thoughts on the leadership of the late Sultan Haji Omar ‘Ali Saifuddien, the 28th Sultan of Brunei, concerning aspects of education, peace and prosperity in the nation, strengthening of Islamic teachings, compassion towards the elderly, as well as Bruneian royal customs. All these views and thoughts contribute to enhancing the image of Bruneian Malay civilisation in particular, and the Malay people in general. Full text: PDF